Měnová politika EU - Jandová, Dagmar (Univerzita Pardubice, 2006)
Cílem bakalářské práce je analýza měnové politiky Evropské unie, respektive eurosystému a Evropské centrální banky. První část práce popisuje systém emise eura a způsob, jak se euro dostalo a dostává oběhu. Dále charakterizuje strategii Evropské centrální banky, nástroje a základní principy při provádění její monetární politiky v prostředí nové společné měny euro. Součástí práce je i zhodnocení působnosti Evropské centrální banky, je popsán vývoj ekonomických indikátorů a rovněž dopady zavedení společné měny. Česká republika je na cestě do Evropské měnové unie, závěr práce je proto věnován perspektivám přístupu k euru.

The objective of this bachelor work is the analyse of the single Monetary Policy of European Union, Eurosystem and The European Central Bank respectively. First part of the work describes the system of euro issuing and the ways how was euro put and is put into circulation. Further the strategy, instruments and basic principles to conduct Monetary Policy are characterised for new common currency – euro. This bachelor work includes the evaluation of European Central Bank’s activity. Development of selected economic indicators and effect of single currency establishment are also described. Czech Republic is on its journey to the European Monetary Union, so the final part of this work engages in perspectives of accepting the euro as its currency.
Monetary policy of EU
Keywords: European Union; European Central Bank; Eurosystems; Monetary Policy; Czech Republic; Evropská Unie; Evropská centrální banka; Eurosystém; EURO; měnová politika; Česká Republika